Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/anie.201306911
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Five‐Membered Osmacycloallenes and Conversion into Six‐Membered Osmacycloallenes

Abstract: Details of the preparation and characterization of 4 and 5 can be found in the Supporting Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Furthermore, in the case of model complex 4’ , the strain energy was calculated to be 3.1 kcal mol −1 . These DFT results agree well with previous reports, which showed that introduction of a transition‐metal atom or a main‐group heteroatom is an efficient strategy to reduce the inherent ring strain in cycloallenes …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, in the case of model complex 4’ , the strain energy was calculated to be 3.1 kcal mol −1 . These DFT results agree well with previous reports, which showed that introduction of a transition‐metal atom or a main‐group heteroatom is an efficient strategy to reduce the inherent ring strain in cycloallenes …”
Section: Resultssupporting
confidence: 92%
“…The structurald ata indicate that 3a is the first iso-metallapyridinium with form IV (Scheme 1), which is closely related to the iso-metallabenzenes.I ti sw orth noting that the Os1-C1-C2 angle (150.5(6)8)d eviates considerably from linearity and is even smaller than those of reported six-membered iso-metallabenzenes (155.1 (8)8 [5b] and 158.5(3)8 [5c] and iso-metallabenzenones (152.7(5)8 and 151.1(2)8). [6] This is further support that resonance form 3A is an important contribution to the overall structure of complex 3a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures with CCC unit in five‐membered metallacycles, e.g., metallacycloallenes12 and metallacyclocumulenes,13 have been reported experimentally and theoretically. In contrast, the similar structure with a MCC unit in a five‐membered ring has only one example reported by us recently 14…”
Section: Methodsmentioning
confidence: 82%